Leveraging L1 folklore: enhancing fictional narrative writing with metacognitive strategies in blended learning environments - Hellystia, Devi; Hermawati, Sri (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study investigates the efficacy of integrating metacognitive strategies and L1 folklore in enhancing English as a Foreign Language (EFL) fictional narrative writing within a blended learning framework. Conducted across 40 Indonesian university students, the quasi-experimental design employed pre and post-tests to measure improvements. Metacognitive techniques (planning, drafting, peer review, self-reflection, and revising) and narrative dimension assessments (voice, characterisation, mood, language, dialogue, story, setting, image, and plot) were applied. A significantly higher rate of EFL narrative writing skill development was observed following the intervention, with 55% of students reaching a very good level and 42.5% getting an excellent level. This highlights the effectiveness of metacognitive strategies in managing time constraints and leveraging L1 folklore to enrich narrative writing. The findings suggest potential long-term benefits and emphasise the need for tailored strategies consistent with cultural contexts. Recommendations include targeted exercises, personalised approaches, peer collaboration, and sustained exposure to L1 folklore to optimise EFL narrative skills. In conclusion, integrating metacognitive strategies and cultural elements enhances EFL education, offering a tailored approach to narrative writing for academic success, particularly considering the needs of Indonesian students in blended learning environments.